On the Quality of Medical Examination: Diagnostic Significance of the Survey Method for Detecting the Probability of Cardio-Cerebral Symptoms - A. M. Kalinina; K. A. Antonov; B. E. Gornyi; I. I. Dubovoj; O. M. Drapkina (Рациональная фармакотерапия в кардиологии)
Aim. To evaluate the effectiveness of the survey method for detecting the probability of cardio-cerebral symptoms and diseases as an indicator of the quality of its use in the framework of medical examination.Material and methods. An analysis of the results of automated survey of all people who passed medical examination in 2018 was carried out in the pilot Bryansk polyclinic in order to identify the likelihood of cardio-cerebral symptoms and anamnesis of coronary heart disease and cerebrovascular diseases.Results. Clinical examination coverage in the pilot clinic was 87.0%. A total of 7588 people were surveyed and interviewed, 4980 women and 2608 men; the majority of those surveyed (69.7%) were under the age of 60 years. The probability of having angina according to the automated survey was found in 3.7% of patients, and in 2.5% it was detected for the first time, i.e. cases of early detection made up the majority (69.2%). The proportion of first-time symptoms was particularly high in young patients (91.2%), which is especially important from the point of view of timely prevention. Neurological symptoms according to the automated survey were detected in 11.7% of the examined patients, and in 10.8% they were detected for the first time, i.e. also in the majority of patients with these symptoms (92.4%). High detection of cardio-cerebral symptoms in young people without a previous history of coronary heart disease and cerebrovascular disease was demonstrated.Conclusion. The clinical and organizational feasibility of the questionnaire method is shown in the framework of phase 1 of the clinical examination of the adult population performed in an automated questionnaire mode. This will eliminate the subjectivity in the interpretation of responses and provide an opportunity to use the survey data in the formation of target groups for additional tests that will surely improve the quality of medical examination and cardio vascular diseases prevention in outpatient medical care.